Peningkatan Pengetahuan Asam Urat Melalui Edukasi Dan Intervensi Herbal Di Rt 06 Kelurahan Ponorogo Kecamatan Lubuklinggau Utara II - Meilando, Idhar; Andrichan, Susan; Diantara, Tenzipa; Andriyanti, Wenny; Murwati, Murwati; Rohani, Tuti; Azissah, Danur (LPPM Universitas Dehasen Bengkulu, 2025)
Uric acid disease is the end result of purine metabolism that can cause inflammation in the joints, known as gout. This study aims to improve the community's understanding of gout, including its causes, symptoms, prevention, and treatment, as well as promote the use of herbal concoctions and rheumatic exercises as preventive and curative measures. The methods used included counseling, demonstration of making herbal concoctions made from ginger, and education on rheumatic exercises in RT 06 Ponorogo Village, Lubuklinggau Utara II District. Evaluation was conducted through pre- and post-activity surveys to assess changes in the level of knowledge and behavior of the community. Results showed that the educational activities significantly improved the community's understanding of gout and implementation of a healthy lifestyle, including a low-purine diet and physical activity. The discussion highlights the importance of a community-based approach involving collaboration between the community, health workers and educational institutions to reduce the prevalence of gout. Follow-up is needed in the form of continuous monitoring and development of similar programs in other areas.